-3z-1=8-2z

Simple and best practice solution for -3z-1=8-2z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3z-1=8-2z equation:


-3z-1=8-2z

We simplify the equation to the form, which is simple to understand
-3z-1=8-2z

We move all terms containing z to the left and all other terms to the right.
-3z+2z=+8+1

We simplify left and right side of the equation.
-1z=+9

We divide both sides of the equation by -1 to get z.
z=-9

See similar equations:

| 17+(-10.8)=47+18 | | 5p+1=8p-32 | | 1.3(2x-5)=0.9x+2 | | 4(x)+y=25 | | n-0.4=8 | | p-0.50=4.35 | | P-0.50=4.36 | | 8x^2+5y=4 | | 300=4.5*p | | -8y^2-6y-10=0 | | (3x+2y)(5x-3y)=9 | | 17+(-6n)=47+10n | | -349=x(-431) | | -9+24x=2(-5+12x) | | -2a+5a+9=0 | | 12r+r-9s+3r= | | 17+6n=47+10n | | z^4-(5iz^2)-4=0 | | 8t-3t+6u-6u-5t= | | 106x=250 | | 106*8=250 | | 3x-y+2z=7 | | 8x-6y-x-4y= | | 4x+1.0=6 | | 5(-6-3a)=3(8+7a) | | p+0.01x=40 | | m+5m+3n-n= | | 2(3+5r)+6=4(2r+5)+6 | | 2x+19=-4-3x | | -16z-15=13z | | a+7b+6c=-7 | | 5+4(7+9)= |

Equations solver categories